Endurance training organization in elite endurance athletes - From description of best practice towards Iidividualized prescription - Sylta, Ø. (University of Agder, Faculty of health and sport science, 2017)
Purpose: The overall objective of this thesis isto contribute to a more detailed understanding of the relationship between endurance training organization and adaptive responses. Three independent studies, and five original papers, have been published towards this objective. Peer-reviewed studies describing training characteristics in elite endurance athletes have been published since the 1980`s. In these studies, different methods of quantifying training patterns during longer time frames have been used, with athlete self-report (SR) in training diaries being the most common. While extensively used, athlete SR diary data has not been evaluated for accuracy and validity. In addition, there are several pitfalls concerning quantification of training intensity distribution (TID). The aims of papers Iand IIwere therefore 1) to validate the accuracy of SR training duration and intensity distribution in elite endurance athletes, and 2) compare three methods of TID quantification employed byelite endurance athletes. Results from these two methodological papers secured a fundamental platform for analysis of further training-characteristicinstudies including reliable methodological interpretations, during an annual cycle in World-Class athletes. The aim of paper IIIwas to describe training characteristics across the annual cycle in Olympic and World Champion endurance athletes. Through observations of high intensity training (HIT) organization patterns in paper III, we formulated hypotheses to be tested experimentally. The aim of paper IVwas to compare the effects of different intensity zone periodization models during 12 weeks on endurance adaptions in well-trained cyclists. Finally, the aim of paper Vwas toquantify the time-course of developmentof performance, physiological and hormonal responses during a 12-week HIT period ingroups prescribed different interval training prescriptions.